Peningkatan Peran Teknologi Informasi Dalam Pembangunan Wilayah Kota/Kab. Bekasi - Kusdarnowo Hantoro; Rena Nugraini Dwi Saputri; Reflon Arnoldi Siagian; Muhammad Ardika Putra Maulana; Muhammad Fadli Absari; Mohammad Irsyad Suryanata; Sheila Mohammad; Malik Alfauziy Hermawan; Fadli Alif Prianda; Rizky Ahmad Faisal; Rafli Pramudya Putranto; Ridho Robbani (Journal Of Computer Science Contributions (JUCOSCO), 2025)
The development of information technology has encouraged local governments and communities to adapt to various digital innovations in order to improve the quality of public services and environmental security. Mustika Jaya Sub-district as an urban area in Bekasi City has significant potential in the utilization of information technology, yet still requires the strengthening of understanding and implementation of structured technology systems, particularly related to area security monitoring. This article discusses the implementation of a web-based CCTV system as an effort to enhance the role of information technology in regional development through the Community Service Program (KKN) conducted by Group 10 of Universitas Bhayangkara Jakarta Raya in Mustika Jaya. The method used is a descriptive approach through several stages, namely situation analysis, program design, implementation of installation and socialization, and evaluation of the benefits perceived by the community partners and students. The main activities include site survey, coordination with local government officers, installation of CCTV devices and supporting software, development of a monitoring system, socialization of CCTV usage to officers and residents, and community service activities such as environmental clean-up. The results show that this program successfully increases the understanding of local officers regarding the function and operation of CCTV, strengthens the capability of real-time environmental monitoring, and encourages public awareness on the importance of utilizing information technology to support security and public order. For students, this program provides hands-on experience in applying information technology knowledge, developing communication and teamwork skills, and obtaining a deeper understanding of social dynamics within the community. In the future, strengthening network infrastructure, expanding CCTV installation points, integrating the monitoring system with village information services, and improving digital literacy are recommended in order to ensure that the utilization of information technology can contribute more sustainably to the development of Mustika Jaya and its surrounding areas.